Properties of the magnetopolaron in a triangular quantum well - 李亚利 单淑萍 (Journal of semiconductors, 2015)
We study the properties of the magnetopolaron in a triangular quantum well within LLP variational method. At different electron-phonon coupling strength, we derive the relations between the ground state energy, the ground state binding energy with the electron areal density and the cyclotron frequency of magnetic field, respectively. Our numerical results show that the ground state energy is an increasing function of the electron areal density and the cyclotron frequency of the magnetic field. However, the ground state binding energy is a decreasing function of those.